2016
DOI: 10.1128/jcm.03345-15
|View full text |Cite
|
Sign up to set email alerts
|

Do Staphylococcus epidermidis Genetic Clusters Predict Isolation Sources?

Abstract: Staphylococcus epidermidis is a ubiquitous colonizer of human skin and a common cause of medical device-associated infections. The extent to which the population genetic structure of S. epidermidis distinguishes commensal from pathogenic isolates is unclear. Previously, Bayesian clustering of 437 multilocus sequence types (STs) in the international database revealed a population structure of six genetic clusters (GCs) that may reflect the species' ecology. Here, we first verified the presence of six GCs, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 49 publications
5
47
0
Order By: Relevance
“…Regarding genetic cluster analysis, consistent with previous reports, we found that 93% of isolates tested were GC1 or GC5 or GC6 ( 61 , 79 ). Although trends were noted with respect to specific genetic clusters and high- or low-shear isolates (e.g., for GC1 and high shear, n = 8; for GC1 and low shear, n = 16), none of these associations were statistically significant.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Regarding genetic cluster analysis, consistent with previous reports, we found that 93% of isolates tested were GC1 or GC5 or GC6 ( 61 , 79 ). Although trends were noted with respect to specific genetic clusters and high- or low-shear isolates (e.g., for GC1 and high shear, n = 8; for GC1 and low shear, n = 16), none of these associations were statistically significant.…”
Section: Discussionsupporting
confidence: 91%
“…Although trends were noted with respect to specific genetic clusters and high- or low-shear isolates (e.g., for GC1 and high shear, n = 8; for GC1 and low shear, n = 16), none of these associations were statistically significant. However, two previous reports of S. epidermidis isolates from New York and Illinois found an association between GC5 and the presence of icaADBC ( 61 , 79 ). Our data are consistent with these observations in that 16/17 (94%) of the GC5 isolates in our study carried icaADBC , whereas only 33% of the isolates overall carried this locus .…”
Section: Discussionmentioning
confidence: 78%
“…In light of the current challenges facing clinical microbiology and professionals addressing control of infectious diseases, the comprehensive article by Tolo and colleagues included in this issue of Journal of Clinical Microbiology presents an interesting method for simplifying the identification of S. epidermidis genotypes in the clinical setting (27). By analyzing seven single nucleotide polymorphisms (SNPs), these researchers were able to accurately assign 545 (94%) of 578 sequence types to six genetic clusters (GCs), which were hypothesized to reflect three different sources of isolates: blood isolates representing true infection, blood isolates representing contaminants, and carriage isolates from nonhospital sources.…”
mentioning
confidence: 99%
“…From the phylogenetic tree, we found the ST2 isolates had an extremely short evolutionary distance from each other. The genetic markers mec A and ica A, which are used to predict the antimicrobial resistance and biofilm phenotypes, have been shown to be more common in hospital isolates than in non-hospital isolates; however, these markers have much less power to distinguish infection isolates from commensally available isolates that contaminate clinical specimens [41]. According to the enrichment analysis, we found it was impossible to distinguish the strains of blood from that of skin, both of which had a similar lifestyle and genetic background.…”
Section: Discussionmentioning
confidence: 99%
“…Whole genome sequencing has been proved to be a more powerful routine diagnostic tool than the traditional MLST or RT-PCR because it can rapidly identify the infection source and antibiotic resistance in an affordable manner [42, 43]. As more genetic data of S. epidermidis have been available and new machine learning algorithm is developed [41], WGS may help to predict the infection isolation sources and antibiotic resistance in a quicker and more accurate manner.…”
Section: Discussionmentioning
confidence: 99%